WANITA, INDUSTRIALISASI DAN NILAI KELUARGA - Effendy, Muhadjir (Jurnal Bestari, 1994)
Industrialization process happens in many countries has given influence to the deviation of the women role. Women prefer working outside. So it causes a degradation of family values, therefore, it necessary to anticipate the revitalization steps of women role in household.